Removal of reactive yellow (RY) AZO dye using activated carbon synthesized from fire stick wood - V. S. Praveen, B; Bhanu Radhika, G; Vamsi Krishna, P (International Journal of Engineering and Technology, 2018)
In the present work we synthesized activated carbon using fire stick wood. For the synthesis chemical activation method is employed using phosphoric acid. Various parameters which influence the adsorption process such as agitation time, adsorbent dosage, initial dye concentration, volume of RY dye solution and pH were studied. Studies showed that 40 mg of adsorbent with 240 micron size was found to remove around 96.76% of dye. Increase in adsorption with the increase in dosage of the adsorbent and decrease in size of the particle, initial concentration and increase in pH of the solution 3 to 6. The obtained results show that activated carbon synthesized from fire wood is effective in the removal of the dye from aqueous solution.Â Â